MENTAL HEALTH AND HIGHER EDUCATION: (RE)THINKING THE CONCEPT OF HEALTH AND PRODUCTIVITY WITHIN CONTEMPORARY UNIVERSITIES FROM A PHENOMENOLOGICAL LOOK - de Azevedo Gomes, Lorena; Lima do Nascimento, Crisóstomo (LINKSCIENCEPLACE, 2026)
This work proposes to (re)think the concepts of health and productivity in contemporary times within universities from a phenomenological approach, based on the assumption that we are crossed daily by the logic of performance and production, as highlighted by the author Han (2015), with the emerging problematization of the idea of health as a synonym for production, that is, in which a being is healthy only if it is productive. In this way, not (re)producing unrestrainedly according to the logic of capital would be the same as being errant, deviant, inept, abnormal and useless. This problem highlights the emergence of a view on productivity from another ontological status, different from the majority capitalist production that maintains the dominant/subordinate dichotomy, objectifying and making the latter sick so that it meets the demands of the dominant being, but rather, from the poietic production that occurs through a contemplative, creative and authentic experiential event, which corroborates the integrality of subject and object, thus providing a less unhealthy relationship between being and things. Therefore, the aim of this work is to understand the relationship between mental health and productivity in contemporary higher education and to contribute with another perspective on the concept of production as poiesis. The methodology used refers to a literature review with reference authors on the topic explained here, such as Han (2015, 2018), Heidegger (2010) and Foucault (1961, 1979). However, it is clear how looking at health as a synonym for productivity in capitalist logic can lead to psychological suffering, with the emergence of (re)thinking the concept of productivity from another ontological status that contributes to a creative process of preservation of the student’s autonomy and mental health in their academic trajectory.